Advanced Issues in Property Valuation : A Textbook - Lind, H., (Hans), author 642036; Nordlund, Bo, author 642037 (Hoboken, NJ : Wiley-Blackwell, 2021)
"There are a number of good basic textbooks in property valuation, e.g. Property Valuation by Peter Wyatt or the Appraisal Institutes classic book The Appraisal of Real Estate. These books presents basic concepts and valuation methods with a focus on what you need to know to work with valuation issues in the real estate sector, either as a producer of valuations or in a position where you use valuations and need to understand and evaluate valuations. This book has been written as a type of "advanced" textbook that problematize a number of the issues that are presented in the basic textbooks. Things are in reality often not so clear as they are in the basic textbooks. There are different views of how useful different concepts and methods really are. Some of these controversies typically surface in specific episodes on the market, e.g. after a crash on the market or in situations where there seem to be very optimistic views among actors in the market that may raise concerns whether e.g real estate assets are "over-valued" in the market. Other differences relate to differences between countries and local traditions. Even though there are international cooperation and standardization, such differences still remain. The aim of the book has been to introduce readers to these discussions and to make it possible to have well-informed opinions on these issues. Some advanced textbooks focus on valuation of specific types of properties - from agriculture to hotels or special purpose buildings - but in this book the focus is on what could be called more theoretical or conceptual issues, but also on some normative issues related to governance and the role of the valuer"--